2016
DOI: 10.1103/physrevc.94.054311
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Kr70 and isospin symmetry in the T=1 fpg shell nuclei

Abstract: The recoil-β tagging technique has been used in conjunction with the 40 Ca( 32 S ,2n) reaction at a beam energy of 88 MeV to identify transitions associated with the decay of the 2 + and, tentatively, 4 + states in the nucleus 70 Kr. These data are used, along with previously published data, to examine the triplet energy differences (TED) for the mass 70 isobars. The experimental TED values are compared with shell model calculations, performed with the JUN45 interaction in the fpg model space, that include a J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…This picture is found across all the mass regions studied to date, irrespective of mass, valence space [i.e., dominant orbital(s)], proximity to shell closures, or degree of deformation or collectivity. The V (2) B (J = 0) term we have established in this analysis for A = 18 to 66 is also consistent with that used by Kaneko et al [25] to explain the data of the A = 70 and 74 T = 1 triplets [7,8]. It is clear from our analysis that these INC interactions are required in all orbitals in the valence space.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This picture is found across all the mass regions studied to date, irrespective of mass, valence space [i.e., dominant orbital(s)], proximity to shell closures, or degree of deformation or collectivity. The V (2) B (J = 0) term we have established in this analysis for A = 18 to 66 is also consistent with that used by Kaneko et al [25] to explain the data of the A = 70 and 74 T = 1 triplets [7,8]. It is clear from our analysis that these INC interactions are required in all orbitals in the valence space.…”
Section: Discussionsupporting
confidence: 90%
“…Mirror nuclei and T = 1 triplets have now been studied in detail in the sd, upper-pf , and pf g shells-see, for example, Refs. [6][7][8][9][10]. In these other regions, there is no longer a dominance of a single shell and so all the orbitals should be considered on the same footing.…”
Section: Introductionmentioning
confidence: 99%
“…The A = 70 nuclei have been chosen for this because previous experimental investigations of the Coulomb energy differences of 70 Se and 70 Br found an anomalous behavior [11], which could be interpreted as a shape change between the isobars [12]. Spectroscopy of 70 Kr at T z = −1 was only achieved recently [13,14], but did not allow to probe the nuclear shape and test for a proposed shape change in the mirror pair 70 Se and 70 Kr [15]. Electromagnetic transition matrix elements, on the other hand, also allow for the determination of the shape or deformation of a nucleus.…”
mentioning
confidence: 99%
“…Naturally, the Coulomb force will break the degeneracy, although the underlying wave functions are expected to retain their isospin symmetry. A significant body of work has built up in recent years examining the difference in excitation energies between mirror pairs and complete T = 1 isobaric triplets -see, for example, references [12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. These studies, which have involved a shell-model interpretation, have shown that the electromagnetic effects within the shell-model cannot account alone for the energy differences, suggesting that other effective isospin-symmetry-breaking interactions are missing from the models -see [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%